Behavioral and Neuronal Alterations Following Oral Naphthalene Exposure in Rats - K.S.V.Angu Bala Ganesh; Thirupathirao Vishnumukkala; Prarthana Kalerammana Gopalakrishna; Saravanan Jagadeesan; Dandala Krishna Chaitanya Reddy; Sura Sreenivasulu; Ravindranadh Gandrakota (Malaysian Journal of Science (MJS), 2025)
Naphthalene (NP), a widely used polycyclic aromatic hydrocarbon, is present in various commercial products and environmental pollutants. Despite its established toxicity, its impact on neuronal integrity and behavior remains relatively underexplored. This study investigates oral NP-induced behavioral and neuronal alterations in Sprague Dawley rats. Twenty-five animals were divided into five groups and oral NP was administered at varying doses (200 mg/kg and 400 mg/kg) for 28 days, with post-treatment evaluations up to 42 days. Behavioral assessments using the open field test revealed initial hyperactivity, followed by a progressive decline in locomotion and increased anxiety-related behavior in high-dose groups. Cresyl violet staining of the basolateral amygdala showed significant neurodegeneration, with pyramidal neuronal damage more pronounced in high-dose groups. Statistical analysis was conducted using one-way ANOVA, and post-hoc Duncan’s test was applied to confirm a dose-dependent decrease in neuronal viability (p < 0.05). Post-treatment observations indicated partial behavioral recovery but no significant reversal of neuronal damage. The findings suggest that oral NP exposure induces anxiety-associated behavioral changes and neurotoxicity in the amygdala, potentially affecting emotional regulation. Further investigation is required to assess the long-term effects of oral NP exposure on brain function.